2016
DOI: 10.1177/2158244016659317
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Personality and Parental Confidence in Mothers of School-Aged Children

Abstract: This study explores the relationship between personality and parental confidence among mothers of school-aged children. The relationships between personality and parenting competence and also between parental confidence and parenting competence are established in the literature, but the relationship between personality and parental confidence is little explored. One hundred twenty-one mothers of school-aged children were surveyed regarding their demographics and parenting confidence, and they also completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
1
9
1
1
Order By: Relevance
“…In this review, parental factors were studied in over 50% of the studies (Baker et al, 2013; Cutrona & Troutman, 1986; Dunning & Giallo, 2012; Ercegovac et al, 2013; Gordo et al, 2018; Gou et al, 2019; de Haan et al, 2013; Henney, 2016; Holloway et al, 2005; Jover et al, 2014; Knauth, 2000; Kwok & Li, 2015; Mazur, 2006; McBride, 1989; Murdock, 2013; Salonen et al, 2009; Shrooti et al, 2016; Suzuki et al, 2009; Troutman et al, 2012). Specifically, the parental demographic characteristics education level and ethnic background have been suggested to have a strong impact on PSE (Cutrona & Troutman, 1986; Dunning & Giallo, 2012; Ercegovac et al, 2013; Gordo et al, 2018; Gou et al, 2019; de Haan et al, 2013; Henney, 2016; Hill & Tyson, 2008; Holloway et al, 2005; Kwok & Li, 2015; McBride, 1989; Murdock, 2013; Salonen et al, 2009; Suzuki et al, 2009; Teti & Gelfand, 1991; Troutman et al, 2012). In the current review, three studies reported positive association between a higher education level and higher PSE, whilst five studies reported a null association (Cutrona & Troutman, 1986; Ercegovac et al, 2013; Hill & Tyson, 2008; Holloway et al, 2005; Salonen et al, 2009; Shrooti et al, 2016; Suzuki et al, 2009; Teti & Gelfand, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this review, parental factors were studied in over 50% of the studies (Baker et al, 2013; Cutrona & Troutman, 1986; Dunning & Giallo, 2012; Ercegovac et al, 2013; Gordo et al, 2018; Gou et al, 2019; de Haan et al, 2013; Henney, 2016; Holloway et al, 2005; Jover et al, 2014; Knauth, 2000; Kwok & Li, 2015; Mazur, 2006; McBride, 1989; Murdock, 2013; Salonen et al, 2009; Shrooti et al, 2016; Suzuki et al, 2009; Troutman et al, 2012). Specifically, the parental demographic characteristics education level and ethnic background have been suggested to have a strong impact on PSE (Cutrona & Troutman, 1986; Dunning & Giallo, 2012; Ercegovac et al, 2013; Gordo et al, 2018; Gou et al, 2019; de Haan et al, 2013; Henney, 2016; Hill & Tyson, 2008; Holloway et al, 2005; Kwok & Li, 2015; McBride, 1989; Murdock, 2013; Salonen et al, 2009; Suzuki et al, 2009; Teti & Gelfand, 1991; Troutman et al, 2012). In the current review, three studies reported positive association between a higher education level and higher PSE, whilst five studies reported a null association (Cutrona & Troutman, 1986; Ercegovac et al, 2013; Hill & Tyson, 2008; Holloway et al, 2005; Salonen et al, 2009; Shrooti et al, 2016; Suzuki et al, 2009; Teti & Gelfand, 1991).…”
Section: Discussionmentioning
confidence: 99%
“… Based on the mean age of children; two studies: Henney, 2016 and Davidson Arad, McLeigh, & Katz, 2018 only reported range of the children these two studies were categorized into the not specific age group. …”
Section: The Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Kaitannya dengan rasa percaya diri adalah bagaimana interaksi social tersebut dapat mendukung ibu sehingga menimbulkan pandangan positif dan rasa percaya diri dalam merawat anak (Saleh, 2011). Sama halnya dengan penelitian yang dilakukan oleh (Henney, 2016) tentang The Relationship Between Personality and Parental Confidence in Mothers of School Aged Children. Studi ini mengeksplorasi hubungan antara kepribadian dan kepercayaan orang tua terhadap anak-anak usia sekolah.…”
Section: Kepercayaan Diri Ibuunclassified